Prostaglandin E2 Signaling Mediates Oenocytoid Immune Cell Function and Lysis, Limiting Bacteria and Plasmodium Oocyst Survival in Anopheles gambiae - Kwon, Hyeogsun; Hall, David R.; Smith, Ryan C. (Frontiers in Immunology, 2021)
Lipid-derived signaling molecules known as eicosanoids have integral roles in mediating immune and inflammatory processes across metazoans. This includes the function of prostaglandins and their cognate G protein-coupled receptors (GPCRs) to employ their immunological actions. In insects, prostaglandins have been implicated in the regulation of both cellular and humoral immune responses, yet in arthropods of medical importance, studies have been limited. Here, we describe a prostaglandin E2 receptor (AgPGE2R) in the mosquito Anopheles gambiae and demonstrate that its expression is most abundant in oenocytoid immune cell populations. Through the administration of prostaglandin E2 (PGE2) and AgPGE2R-silencing, we demonstrate that prostaglandin E2 signaling regulates a subset of prophenoloxidases (PPOs) and antimicrobial peptides (AMPs) that are strongly expressed in populations of oenocytoids. We demonstrate that PGE2 signaling via the AgPGE2R significantly limits both bacterial replication and Plasmodium oocyst survival. Additional experiments establish that PGE2 treatment increases phenoloxidase (PO) activity through the increased expression of PPO1 and PPO3, genes essential to anti-Plasmodium immune responses that promote oocyst killing. We also provide evidence that the mechanisms of PGE2 signaling are concentration-dependent, where high concentrations of PGE2 promote oenocytoid lysis, negating the protective effects of lower concentrations of PGE2 on anti-Plasmodium immunity. Taken together, our results provide new insights into the role of PGE2 signaling on immune cell function and its contributions to mosquito innate immunity that promote pathogen killing.